Positive plate, lithium ion battery and electric equipment

By adding thermally conductive composite materials to the active layer of the positive electrode sheet of the lithium-ion battery, the problem of excessive temperature rise in the lithium-ion battery during rapid charging and discharging is solved, and better heat dissipation effect and battery performance are achieved.

CN119852597APending Publication Date: 2025-04-18ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510085729.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The temperature rise of lithium-ion batteries is high during fast charging and discharging, which seriously affects the battery's circulation performance and safety performance.

Method used

A positive electrode sheet is designed, with the active layer containing a thermally conductive composite material, the core is aluminum nitride or boron nitride, and the surface is coated with a conductive coating, such as graphene or carbon nanotubes, to improve thermal conductivity.

Benefits of technology

Through the use of thermally conductive composite materials, lithium-ion batteries can dissipate heat more effectively during fast charging, reduce battery temperature, avoid fire and explosion caused by excessive temperature, and thus improve the battery's circulation and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852597A_ABST
    Figure CN119852597A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of secondary batteries, and particularly relates to a positive plate, a lithium ion battery and electric equipment. The heat-conducting composite material with specific composition is added into the active layer of the positive plate, the inner core of the positive plate is the high-heat-conducting material, and the conductive coating layer is arranged on the surface of the inner core, so that the heat-conducting composite material can be uniformly distributed in the active layer; by means of the high-thermal-conductivity substance, heat generated by fast charging can be transferred outwards and dissipated in time, the temperature of the battery is reduced, the situation that the battery is on fire and explodes due to the too high temperature can be avoided, and the situation that the cycle performance and safety performance of the battery are affected by the too high temperature is prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of secondary batteries, and specifically relates to a positive electrode sheet, a lithium-ion battery and an electrical device. Background Art

[0002] In recent years, with the widespread popularity of portable electronic devices such as smart phones and laptops, and the rapid development of mobile transportation such as new energy vehicles and electric (bicycles), the various performances of lithium-ion batteries have received more and more attention. In order to shorten the charging time and improve the user's consumption experience, the fast charging performance of batteries has gradually become a standard configuration for various electrical devices. Therefore, improving the fast charging performance of batteries is crucial to improving market competitiveness.

[0003] However, there are still some problems with fast charging in the existing battery production technology. This is mainly because the heat dissipation capacity of the electrode is limited during the charging and discharging process. After increasing the fast charging rate of the battery, the battery will heat up seriously. In particular, the temperature of large batteries may exceed 70°C during rapid charging and discharging (normal protection temperature ≤ 60°C). Excessive temperature will cause the electrolyte to decompose and produce side reactions, which will reduce the battery's liquid retention capacity and seriously affect the battery's cycle performance and safety performance. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present application is to overcome the defects of lithium-ion batteries in the prior art such as high temperature rise during rapid charging and discharging, which seriously affects the battery cycle performance and safety performance, thereby providing a positive electrode sheet, a lithium-ion battery and an electrical device.

[0005] To this end, this application provides the following technical solutions:

[0006] According to one aspect of the present application, a positive electrode sheet is provided, comprising:

[0007] The current collector has two opposite surfaces in its thickness direction;

[0008] An active layer is coated on at least one surface of the current collector, wherein the active layer includes a thermally conductive composite material, wherein the thermally conductive composite material includes a core and a conductive coating layer coated on at least a portion of the surface of the core, and the core includes at least one of aluminum nitride or boron nitride.

[0009] In some optional embodiments, the mass proportion of the thermally conductive composite material is 0.55%-3.5% based on the total mass of the active layer. As an example, the mass proportion of the thermally conductive composite material can be 0.55%, 0.85%, 1.0%, 1.3%, 1.5%, 1.8%, 2.0%, 2.35%, 2.55%, 2.85%, 3.0%, 3.25%, 3.5%, or within the range of any of the above values.

[0010] In some optional embodiments, the mass proportion of the core may be 0.5%-3.0% based on the total mass of the active layer. As an example, the mass proportion of the core may be 0.5%, 0.85%, 1.0%, 1.3%, 1.5%, 1.8%, 2.0%, 2.35%, 2.55%, 2.85%, 3.0%, or within a range consisting of any of the above values.

[0011] In some optional embodiments, the conductive coating layer includes at least one of graphene or carbon nanotubes. Preferably, the conductive coating layer includes graphene.

[0012] In some optional embodiments, the average particle size of the core is 50-300 nm. As an example, the average particle size of the core is 50 nm, 80 nm, 100 nm, 130 nm, 150 nm, 180 nm, 200 nm, 230 nm, 250 nm, 270 nm, 300 nm, or within the range of any of the above values.

[0013] In some optional embodiments, the active layer further includes a positive electrode active material, a conductive agent and a binder.

[0014] In some optional embodiments, based on the total mass of the active layer, the mass ratio of the positive electrode active material, the conductive agent, and the binder in the active layer is 95-98.2:0.3-2.0:1.5-3.0. As an example, the mass ratio of the positive electrode active material, the conductive agent, and the binder in the active layer can be 95:2.0:3.0, 96:1.5:2.5, 96.5:1.5:2.0, 97:1.5:1.5, 97.5:0.5:2.0, 98.2:0.3:1.5, or within the range of any of the above values.

[0015] In some optional embodiments, the positive electrode active material is a conventional positive electrode active material in the field, which can be selected according to the specific use requirements of the lithium ion battery. As an example, the positive electrode active material includes but is not limited to at least one of lithium iron phosphate, lithium iron manganese phosphate, and lithium nickel cobalt manganese oxide;

[0016] And / or, the conductive agent is conventional in the field, including but not limited to at least one of conductive carbon black, carbon nanotubes, carbon fibers, and graphene;

[0017] And / or, the binder is conventional in the field, including but not limited to at least one of polyvinylidene fluoride, polyurethane, and polyvinyl alcohol.

[0018] According to another aspect of the present application, a lithium-ion battery is provided, comprising the above-mentioned positive electrode sheet.

[0019] In some optional embodiments, a negative electrode sheet, a separator and an electrolyte are also included.

[0020] According to another aspect of the present application, there is provided an electrical device comprising the above-mentioned lithium-ion battery.

[0021] Those skilled in the art can understand that the lithium-ion battery provided in the present application includes a pole core, an electrolyte, structural parts and a shell, etc., and the pole core, electrolyte and structural parts are all in the shell; the pole core includes the positive electrode sheet, negative electrode sheet and diaphragm provided in the above aspects of the present application, and the three can be made into a pole core by lamination or winding and formed by high-temperature hot pressing. During the battery charging and discharging process, lithium ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet, and the electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The diaphragm is arranged between the positive electrode sheet and the negative electrode sheet, which mainly plays the role of preventing the positive and negative electrodes from short-circuiting, and at the same time allows lithium ions to pass through.

[0022] As an example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is arranged on any one or both of the two opposite surfaces of the negative electrode current collector. The material, composition and manufacturing method of the negative electrode sheet used in the lithium ion battery of the present application may include any technology disclosed in the prior art.

[0023] The material and shape of the separator used in the lithium ion battery of the present application are not particularly limited, and may include any technology disclosed in the prior art.

[0024] The electrolyte used in the lithium-ion battery of the present application may include any technology disclosed in the prior art.

[0025] The technical solution of this application has the following advantages:

[0026] The positive electrode sheet provided by the present application includes: a current collector having two opposite surfaces in its own thickness direction; an active layer coated on at least one surface of the current collector, wherein the active layer includes a thermally conductive composite material, wherein the thermally conductive composite material includes a core and a conductive coating layer coated on at least part of the surface of the core, and the core includes at least one of aluminum nitride or boron nitride. The positive electrode sheet provided by the present application adds a thermally conductive composite material to the active layer, wherein the core is a high thermal conductivity material, and the conductive coating layer is arranged on the surface of the core, so that the thermally conductive composite material can be evenly distributed in the active layer. After being made into a lithium-ion battery, in the battery fast charging test, the heat generated by the fast charging can be timely transferred and dissipated outward through the high thermal conductivity material, thereby reducing the battery temperature, avoiding the battery from catching fire or exploding due to excessive temperature, and preventing the excessive temperature from affecting the battery cycle performance and safety performance. Specifically, a conductive coating layer is provided on the surface of the inner core mainly because the aluminum nitride particles or boron nitride particles themselves are not conductive. If they are added directly, they will occupy the binder and conductive agent of the active layer itself, and the aluminum nitride particles or boron nitride particles will adhere and agglomerate with the binder, making it unevenly dispersed, reducing the conductivity of the active layer, increasing the electrode resistance, and increasing the temperature rise during the battery charging and discharging process, affecting the battery performance. When using thermally conductive composite materials, since the aluminum nitride or boron nitride inner core is coated in the conductive coating layer, after being added to the active layer, it no longer occupies the binder and conductive agent of the active layer itself, and does not affect the original conductivity of the electrode.

[0027] The positive electrode sheet provided in the present application, wherein the conductive coating layer includes at least one of graphene and carbon nanotubes, and graphene and carbon nanotubes can increase partial conductivity, which is beneficial to further improve battery performance.

[0028] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0030] Figure 1 It is a schematic diagram of the structure of the positive electrode sheet provided in the embodiment of the present application;

[0031] Reference numerals:

[0032] 1. Current collector; 2. Active layer; 3. Thermally conductive composite material. DETAILED DESCRIPTION

[0033] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.

[0034] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0035] In the following examples and comparative examples of the present application, unless otherwise specified, "%" represents the mass percentage.

[0036] The thermally conductive composite materials used in the following examples were purchased from Xi'an Qiyue Biotechnology Co., Ltd. according to customized requirements.

[0037] Example 1

[0038] This embodiment provides a positive electrode sheet, and its structural schematic diagram is as follows Figure 1 As shown, it includes a current collector 1, an active layer 2 coated on the surface of the current collector 1, and the active layer 2 includes a thermal conductive composite material 3;

[0039] The preparation method of the positive electrode sheet is as follows:

[0040] (1) lithium iron phosphate, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride are added in a mass ratio of 96.5:1.0:0.5:2.0, N-methylpyrrolidone is used as a solvent, and a thermal conductive composite material accounting for 0.56% of the mass of the active layer is added, the core of the thermal conductive composite material is boron nitride particles with an average particle size of 100 nm, the conductive coating layer is graphene, and the mass proportion of the core in the active layer is 0.5%, and the raw materials are mixed evenly to obtain a positive electrode slurry;

[0041] (2) The prepared positive electrode slurry is coated on one side of an aluminum foil with a thickness of 13 μm. After coating, the electrode sheet is cut, rolled, and die-cut to prepare a positive electrode sheet. The coating surface density of the positive electrode sheet in this application can be 360-400 g / m 2 The compaction density of the positive electrode can be 2.3-2.7g / cm 3 ; The surface density of the positive electrode in this embodiment is 388g / m 2 , compacted density is 2.59g / cm 3 .

[0042] Example 2-Example 12

[0043] Compared with Example 1, the differences between Example 2 to Example 12 are the proportion of the thermally conductive composite material in the active layer, the proportion of the boron nitride core, and the average particle size of the boron nitride core. The specific differences are detailed in Table 1.

[0044] Table 1

[0045]

[0046] Comparative Example 1

[0047] This comparative example provides a positive electrode sheet, which is different from Example 3 in that no thermally conductive composite material is added to the active layer.

[0048] Comparative Example 2

[0049] This comparative example provides a positive electrode sheet, which is different from Example 3 in that boron nitride particles without a conductive coating layer are directly used in the active layer as a thermally conductive composite material, and the addition amount of the boron nitride particles (average particle size 300nm) accounts for 0.5% of the mass of the active layer.

[0050] Comparative Example 3

[0051] This comparative example provides a positive electrode sheet, which is different from Example 3 in that boron nitride particles (average particle size 300 nm) and graphene are used instead of the thermally conductive composite material, wherein the boron nitride particles account for 0.5% of the mass of the active layer, and the graphene accounts for 0.06% of the mass of the active layer.

[0052] Embodiment 13

[0053] This embodiment provides a positive electrode sheet, and its structural schematic diagram is as follows Figure 1 As shown, it includes a current collector 1, an active layer 2 coated on the surface of the current collector 1, and the active layer 2 includes a thermal conductive composite material 3;

[0054] The preparation method of the positive electrode sheet is as follows:

[0055] (1) lithium iron phosphate, conductive carbon black, carbon nanotubes, and polyvinylidene fluoride are added in a mass ratio of 96.5:1.0:0.5:2.0, N-methylpyrrolidone is used as a solvent, and a thermal conductive composite material accounting for 0.56% of the mass of the active layer is added, the core of the thermal conductive composite material is aluminum nitride particles with an average particle size of 100 nm, the conductive coating layer is graphene, and the mass proportion of the core in the active layer is 0.5%, and the raw materials are mixed evenly to obtain a positive electrode slurry;

[0056] (2) The prepared positive electrode slurry is coated on one side of an aluminum foil with a thickness of 13 μm. After coating, the electrode sheet is cut, rolled, and die-cut to prepare a positive electrode sheet. The coating surface density of the positive electrode sheet in this application can be 360-400 g / m 2The compaction density of the positive electrode can be 2.3-2.7g / cm 3 ; The surface density of the positive electrode in this embodiment is 388g / m 2 , compacted density is 2.59g / cm 3 .

[0057] Example 14-Example 24

[0058] Compared with Example 13, the differences between Example 14 to Example 24 are the proportion of the thermally conductive composite material in the active layer, the proportion of the aluminum nitride core, and the average particle size of the aluminum nitride core. The specific differences are detailed in Table 2.

[0059] Embodiment 25

[0060] The difference between Example 25 and Example 13 is that the conductive coating layer in the active layer is carbon nanotubes.

[0061] Table 2

[0062]

[0063] Comparative Example 4

[0064] This comparative example provides a positive electrode sheet, which is different from Example 15 in that aluminum nitride particles without a conductive coating layer are directly used in the active layer as a thermally conductive composite material, and the added amount of aluminum nitride particles (average particle size 300nm) accounts for 0.5% of the mass of the active layer.

[0065] Comparative Example 5

[0066] This comparative example provides a positive electrode sheet, which differs from Example 15 in that aluminum nitride particles (average particle size 300 nm) and graphene are used instead of the thermally conductive composite material, wherein the aluminum nitride particles account for 0.5% of the mass of the active layer, and the graphene accounts for 0.06% of the mass of the active layer.

[0067] Test Case

[0068] The specific steps for making lithium-ion batteries are as follows:

[0069] The positive electrode sheets, separators, and negative electrode sheets prepared in the above-mentioned embodiments and comparative examples are stacked to form a core, and the positive and negative electrode ears of the core are welded to the positive and negative electrode covers, and the core is placed in a housing, and electrolyte is injected to perform formation, capacity division, and other processes to form a lithium-ion battery (rated capacity 198Ah). The specific steps are as follows:

[0070] Preparation of negative electrode sheet: artificial graphite, conductive carbon black, styrene-butadiene rubber, and sodium carboxymethyl cellulose are added in a mass ratio of 96:1.0:1.6:1.4, and deionized water is used as a solvent to obtain negative electrode slurry. The prepared negative electrode slurry is coated on one side of a current collector copper foil with a thickness of 6 μm, and then baked, slit, rolled, and die-cut to prepare a negative electrode sheet. The coating surface density of the negative electrode sheet in this application can be 150-200 g / m 2 The compaction density of the negative electrode sheet can be 1.4-1.7g / cm 3 ; The surface density of the negative electrode sheet in this test example is 171g / m 2 , compacted density is 1.6g / cm 3 .

[0071] Diaphragm: A 7μm thick PE base film is used, and a 1.5μm thick ceramic layer (the ceramic layer is made of Al2O3) and a 3μm thick PVDF adhesive layer are coated on both sides of the PE base film.

[0072] Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are mixed in a mass ratio of 1:1:1 to obtain an organic solvent, and the organic solvent is mixed with lithium salt lithium hexafluorophosphate to obtain an electrolyte with a lithium salt concentration of 1 mol / L.

[0073] The lithium-ion batteries including the positive electrode sheets provided in the above embodiments and comparative examples were subjected to charge-discharge and fast-charge cycle tests:

[0074] (1) 1C charge and discharge test

[0075] The lithium-ion battery was subjected to 1C charge and discharge test at 25°C (charge and discharge current was 1C, voltage range was 2.0-3.75V). After 3 cycles of testing, the temperature of the monitoring point in the middle of the large surface of the battery was calculated.

[0076] (2) Battery fast charge cycle test

[0077] The lithium-ion battery was subjected to a fast charge cycle test at 25°C (fast charge adopts a step charge mode, with an average charge current of 4C, a discharge current of 1C, and a voltage range of 2.0-3.75V). After 1000 cycles, the capacity retention rate of 1000 cycles was calculated; the specific operating parameters of the step charge mode are shown in the table below:

[0078] Table 3

[0079] SOC Step charging rate / C Upper limit voltage / V 0%<SOC≤10% 4.889 3.75 10%<SOC≤15% 5.500 3.75 15%<SOC≤20% 5.300 3.75 20%<SOC≤25% 5.110 3.75 25%<SOC≤30% 4.920 3.75 30%<SOC≤35% 4.710 3.75 35%<SOC≤40% 4.550 3.75 40%<SOC≤45% 4.400 3.75 45%<SOC≤50% 4.200 3.75 50%<SOC≤55% 4.000 3.75 55%<SOC≤60% 3.800 3.75 60%<SOC≤65% 3.600 3.75 65%<SOC≤70% 3.400 3.75 70%<SOC≤75% 3.110 3.75 75%<SOC≤80% 2.780 3.75 80%<SOC≤85% 2.250 3.75 85%<SOC≤90% 1.940 3.75 90%<SOC≤95% 1.400 3.75 95%<SOC≤98% 0.700 3.75 98%<SOC≤100% 0.500 3.75

[0080] When the battery is fast-charged, the temperature of the large surface of the battery is monitored in real time through a temperature sensor, and data is recorded to extract the highest temperature during 1,000 cycles.

[0081] The specific test results are shown in the table below:

[0082] Table 4

[0083]

[0084]

[0085] Table 5

[0086]

[0087] It can be seen from the test results of Tables 4 and 5 that compared with the comparative example, the lithium-ion battery made of the positive electrode sheet provided in the embodiment of the present application can effectively reduce the temperature rise of the battery, avoid the decomposition of the electrolyte caused by high temperature, reduce the amount of liquid retention, and thus affect the battery cycle performance. At the same time, it can be seen from the comparison results between the embodiments that by adding different particle sizes and different addition amounts of high thermal conductivity boron nitride and aluminum nitride thermal conductive composite materials, the temperature rise of the battery fast charging process can be reduced. The smaller the boron nitride and aluminum nitride particles, the larger the specific surface area, the more contact points, and the better the heat dissipation effect. For aluminum nitride with the same particle size, the more the amount added, the greater the temperature rise reduction, but at the same time, the amount of aluminum nitride additives must be controlled. Too much addition reduces the battery energy density. By adding thermal conductive composite materials with different particle sizes and different addition amounts, batteries with different heat dissipation effects can be prepared to meet different fast charging performance application requirements. With the development of power batteries in the market, the requirements for charging time are getting higher and higher. Along with the gradual increase in charging rate, the technical solution provided in this application is applied to power batteries with larger capacity. Those skilled in the art can expect that it will also have a good heat dissipation effect during the fast charging process, thereby improving the cycle performance and safety performance of the battery cells and meeting consumers' demand for fast charging performance.

[0088] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A positive electrode sheet, characterized in that: include: The current collector has two opposite surfaces in the thickness direction thereof; An active layer is coated on at least one surface of the current collector, wherein the active layer includes a thermally conductive composite material, wherein the thermally conductive composite material includes a core and a conductive coating layer coated on at least a portion of the surface of the core, and the core includes at least one of aluminum nitride or boron nitride.

2. The positive electrode sheet according to claim 1, characterized in that: Based on the total mass of the active layer, the mass of the thermally conductive composite material accounts for 0.55%-3.5%.

3. The positive electrode sheet according to claim 1, characterized in that: The mass of the core accounts for 0.5%-3.0% of the total mass of the active layer; And / or, the conductive coating layer includes at least one of graphene or carbon nanotubes.

4. The positive electrode sheet according to claim 1, characterized in that: The average particle size of the core is 50-300 nm.

5. The positive electrode sheet according to any one of claims 1 to 4, characterized in that: The active layer also includes a positive electrode active material, a conductive agent and a binder.

6. The positive electrode sheet according to claim 5, characterized in that: In the active layer, the mass ratio of the positive electrode active material, the conductive agent, and the binder is 95-98.2:0.3-2.0:1.5-3.

0.

7. The positive electrode sheet according to claim 5, characterized in that: The positive electrode active material includes at least one of lithium iron phosphate, lithium iron manganese phosphate, and lithium nickel cobalt manganese oxide; And / or, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, carbon fibers, and graphene; And / or, the binder includes at least one of polyvinylidene fluoride, polyurethane, and polyvinyl alcohol.

8. A lithium ion battery, characterized in that: A positive electrode sheet comprising any one of claims 1 to 7.

9. The lithium-ion battery according to claim 8, characterized in that: It also includes a negative electrode sheet, a separator and an electrolyte.

10. An electrical device, characterized in that: Comprising the lithium ion battery according to claim 8 or 9.

Citation Information

Cited By

  • Positive electrode additive and preparation method and application thereof

    CN120749166A